A Simplified Method for Thermally-Induced Volumetric Error Compensation - Lu, Yuxia; Islam, Mohammad Nazrul (Praise Worthy Prize, 2011)
The thermally-induced volumetric error of a machine tool has been recognised as a major contributor to dimensional and geometric errors of component parts produced on it. Consequently, considerable research has focused on compensating for this type of error. The traditional model of compensation for thermally-induced volumetric error of a three-axis machine tool requires measuring 21 geometric error components, which are difficult and time consuming to gather. This paper describes the development of a simplified method of compensating for thermally-induced error based on only three axial positioning errors, which are assumed to be functions of ball-screw nut temperature and travel distance. It is a more efficient and comparatively cheaper method of compensating for thermally-induced error. The results indicate that only a negligible amount of the total dimensional accuracy is sacrificed by adopting the proposed model instead of the traditional model.